2020
DOI: 10.1186/s12866-020-01839-y
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of “kitome” and “splashome” contamination results in lack of detection of a unique placental microbiome

Abstract: Background: A placental microbiome, which may be altered in gestational diabetes mellitus (GDM), has been described. However, publications raising doubts about the existence of a placental microbiome that is different than contaminants in DNA extraction kits and reagents ("kitomes") have emerged. The aims of this study were to confirm the existence of a placental microbiome distinct from contaminants and determine if it is altered in GDM mothers. Results: We first enrolled normal weight, obese and GDM mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 61 publications
4
110
0
Order By: Relevance
“…The 16S rRNA gene amplification and sequencing approach used in most studies is so sensitive that it detects dozens if not hundreds of microbial taxa no matter if a sample is added or not (the “kitome”) [ 16 , 17 ]. The approach requires careful sampling, proper controls, bioinformatic tools, and objectivity during the analysis to identify taxa truly overrepresented in samples as compared to controls [ 18 25 , 27 , 28 , 38 , 39 ]. Microscopy, qPCR techniques, and culture have also been used to confirm the presence of bacteria [ 27 , 38 ].…”
Section: The Prenatal Microbiome Debate In the Light Of Karl Popper’smentioning
confidence: 99%
See 1 more Smart Citation
“…The 16S rRNA gene amplification and sequencing approach used in most studies is so sensitive that it detects dozens if not hundreds of microbial taxa no matter if a sample is added or not (the “kitome”) [ 16 , 17 ]. The approach requires careful sampling, proper controls, bioinformatic tools, and objectivity during the analysis to identify taxa truly overrepresented in samples as compared to controls [ 18 25 , 27 , 28 , 38 , 39 ]. Microscopy, qPCR techniques, and culture have also been used to confirm the presence of bacteria [ 27 , 38 ].…”
Section: The Prenatal Microbiome Debate In the Light Of Karl Popper’smentioning
confidence: 99%
“…The findings were therefore not sufficient to challenge sterility of the womb, as sterility is defined as the absence of viable life. Over the years, it also became increasingly obvious that contamination [16,17], or the so called "kitome" [18], represented a major problem when next-generation sequencing and PCR-based approaches were applied to low-biomass samples [19]. Consequently, several subsequent sequencing studies that used strict controls for contamination did not support the presence of microbial DNA in utero [18,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently Rackaityte and colleagues reported bacterial presence via scanning electron microscopy and limited signatures by 16S rRNA sequencing in a similar sample set (12). The discrepancy between our inability to amplify bacterial DNA and the findings by Rackaityte and colleagues exemplifies the debate over the existence of an in utero microbiome, with some studies identifying a low biomass microbiome (13)(14)(15)(16)(17)(18) and others finding no microbial signatures beyond background levels in animals and humans (7)(8)(9)(10)(11)(46)(47)(48). The controversy about the existence of a placental and fetal microbiome cannot be resolved solely with the data presented in this manuscript.…”
Section: Discussionmentioning
confidence: 70%
“…However, they found that the median gene counts for bacterial signal were highest for the maternal side of the placenta regardless of the mode of delivery and indeed detected sporadic bacteria. Olomu et al and Theis et al also used 16S rRNA gene amplicon sequencing of placental parenchyma (villi) with positive and negative controls and did not include maternal decidua in their analyses [ 17 , 18 ]. They found no significant differences in either total biomass or microbial composition when comparing placental samples and negative controls.…”
Section: Group Therapy: Let Us Talk About the Differencesmentioning
confidence: 99%